Comparing parental involvement for international academic Olympians from Europe, Scandinavia, and America - Campbell, J. R.; Freeley, M. E.; O`Connor-Petruso, S. (Talent Development & Excellence, 2012)
This cross-cultural article examines the family life of 576 parents of the academic Olympians from the United States, Germany, and Finland. We examined the factors that contribute to the adult productivity of these gifted individuals. We found that socio-economic status is a substantial predictor of many of the parental variables we studied. The family dynamics that consist of positive and negative sets of parental factors unearthed a number of significant combinations. One set deals with the press for literacy and its correlations with parental support and expectations. The other set centers around pressure, help, and supervision. Overall, we uncovered distinctive roles for these Olympian mothers and fathers that have directly or indirectly affected their children`s scholarly productivity.